LIFE AND SCIENTIFIC ACHIEVEMENTS OF TRYPHON MAKSYMOVYCH BASHTA - Bashta, Olena; Dzhuryk, Olena; Romanenko, Victor; Dzhuryk, Natalia (Proceedings of National Aviation University (archive), 2016)
The article considers life and scientific achievements of T. M. Bashta (1904 -1987), a product manager of aircraft industry and the founder of home scientific school of industrial hydraulics. Two strategic branches – machine tool-building and aeronautic – are indebted exactly to him for its advance.